Association of the epidemiological profile with the clinical outcome of patients with COVID-19 at a university hospital in the first and second wave of infection (Research, Society and Development, 2023)
Objective: To associate the epidemiological profile with the clinical outcome of patients with COVID-19 at a university hospital during the periods of hospitalization comprised by the first and second wave of the infection in Brazil. Methodology: Retrospective, quantitative, descriptive and comparative cohort - ethically approved, carried out in a university hospital that is a reference in COVID-19 care for patients admitted to Intensive Care Units in the first and second wave in Brazil, with statistical application of Binary Logistic Regression (p≤0.05; 95%CI) and descriptive analysis of the association between the epidemiological profile and the clinical outcomes calculated separately in the waves. Results: In the first wave (n=46), age was the only significant predictor for association with the outcome, which the chance (Odds Ratio= 1.0897) of death corresponded to 1.08 times greater as each year of age increases. Predictors could not explain outcomes in the second wave (n=57). Deaths, lower education, more advanced age groups, men and mixed race were the most prevalent among the samples. Discussion: The epidemiological change for the second wave was influenced by national vaccination and by socioeconomic, cultural and political factors experienced in Brazil, changing the influence of some predictors in the second wave. Conclusion: Age was the decisive factor to influence the clinical outcome of patients. In addition, as well as the trends discussed in the most current epidemiological studies, brown men over 60 years of age were the most affected by COVID-19 during the first and second waves of infection in Brazil.